Educação do campo e educação matemática: o significado do estudo da matemática em uma escola multisseriada de um distrito rural de Feira de Santana - Ba - Alexandre, Fernando dos Santos (2020)
This study arises from questions related to the challenges of Mathematics Education compared to the social, political, economic and educational reality of the countryside and its Multisiered Classes. The research aims to "analyze the meaning that teachers and responsible of students in the multiserial class of a rural district in the municipality of Feira de Santana - BA, attribute to the study of Mathematics". It is a qualitative research that brings as categories of analysis, Rural Education (CALDART, 2012; SOUZA, 2012), Critical Mathematical Education (SKOVSMOSE, 2001; FRANKENSTEIN, 1983), Multiseriate Classes (JANATA and ANHAIA, 2015; HAGE, 2011; SANTOS, 2016) and that had as an empirical field, the multiseriate class with students from the 1st to the 5th year of a school in the district of Matinha in the municipality of Feira de Santana, in the interior of Bahia. The subjects participating in this research were: the teacher of the multiseriate class, the classroom assistant, the general services assistant of the school and the parents and responsible of students of the researched class. The data collection instruments were: classroom observations; questionnaires to survey the socio-economic-cultural profile of the community and the participating subjects; semi-structured interview with the teacher; and the realization of two sections of Focus Group with the parents and responsible of the students in the researched context. From the data collected, regarding the meaning of studying mathematics for the parents and responsible of the students of the school studied, there is recognition of the relevance of school mathematical knowledge in the face of the disadvantages of life in society, work and community life in the countryside. The subjects involved in the research demonstrated the use of mathematical knowledge in daily tasks, and the understanding of everyday issues related to it, however, point to numerous difficulties in perceiving the harmony of this mathematics learned in everyday life, with the mathematics worked in the school universe. We conclude from the analysis of data and bibliographic research on the subject, that it is necessary to overcome gaps in teacher training, a pedagogical practice contextualized in the daily lives of these subjects and the support of educational policies for the reality of multiserial classes in the field.